Andrographolide Protects against HG-Induced Inflammation, Apoptosis, Migration, and Impairment of Angiogenesis via PI3K/AKT-eNOS Signalling in HUVECs - Mingxia Duan; Heng Zhou; Qingqing Wu; Chen Liu; Yang Xiao; Wei Deng; Qizhu Tang (2019)
Andrographolide (Andr) is a major component isolated from the plant Andrographis paniculata. Inflammation, apoptosis, and impaired angiogenesis are implicated in the pathogenesis of high glucose (HG)-induced injury of vascular endotheliocytes. Our study is aimed at evaluating the effect of Andr on HG-induced HUVEC injury and the underlying mechanism. HUVECs were exposed to HG levels (33 mM) and treated with Andr (0, 12.5, 25, and 50 μM). Western blot analysis, real-time PCR, immunofluorescence staining, the scratch test, and the tube formation assay were performed to assess the effects of Andr. We discovered that Andr inhibited the inflammatory response (IL-1β, IL-6, and TNFα), decreased the apoptosis ratio and cell migration, and promoted tube formation in response to HG stimulation. Andr ameliorated the levels of phosphorylated PI3K (p-PI3K), phosphorylated AKT (p-AKT), and phosphorylated eNOS (p-eNOS). The expression of vascular endothelial growth factor (VEGF) protein, a vital factor in angiogenesis, was improved by Andr treatment under HG stimulation. LY294002 is a blocker of PI3K, MK-2206 2HCI (MK-2206) is a highly selective AKT inhibitor, and L-NAME is a suppressor of eNOS, all of which significantly reduce Andr-mediated protective effects in vitro. Hence, Andr may be involved in regulating HG-induced injury by activating PI3K/AKT-eNOS signalling in HUVECs.